Function of Subjects Suffering from Multiple Sclerosis in Balance Tests Following Facilitatory and Inhibitory Kinesiotaping of Gastrocnemius Muscle: Randomized Single-Blind Trial (Pilot Study) - Ghazal Kharaji; Fatemeh Bagheri; Hamzeh Baharlouei (Vesnu Publications, 2016)
Introduction: Multiple sclerosis is a demyelinating disease of the central nervous system. Iran is considered to have a high prevalence of multiple sclerosis. Its consequences are balance deficiency, falling and fracture. Studies have shown that kinesiotaping promotes balance in patients with neurologic disorders. The aim of this study was to evaluate the immediate effect of kinesiotaping in patients with multiple sclerosis. Materials and Methods: ‎The participants were randomly assigned into two groups. One group received facilitation kinesiotaping technique and the other group received inhibition techniques on gastrocnemius. The balance was evaluated using Time Up and Go and functional reach tests before and 30 minutes after taping. The assessor was blind to the method of taping. Results: Within group analyses with paired t-test showed significant improvement in Timed Up And Go and functional reach records following taping in both groups. However, analysis showed no significant difference between the two experimental groups. Conclusion: The results of present study showed that both facilitation and inhibition kinesiotaping technique of gastrocnemius muscle may immediately improve the dynamic balance in patients with multiple sclerosis.